2021
DOI: 10.1097/iae.0000000000003277
|View full text |Cite
|
Sign up to set email alerts
|

UVEITIS AFTER THE BNT162b2 mRNA VACCINATION AGAINST SARS-CoV-2 INFECTION

Abstract: Purpose: To describe uveitis cases after the BNT162b2 mRNA SARS-CoV-2 vaccination.Methods: This is a multicenter, retrospective study. Vaccine-related uveitis diagnosis was supported by the classification of the World Health Organization Adverse Drug Terminology and the Naranjo criteria.Results: Twenty-one patients (23 eyes) with a mean age of 51.3 years (23-78 years) were included. Eight of the 21 patients had a known history of uveitis. The median time from previous to current attack was 1 year (0.5-15 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 25 publications
6
87
3
Order By: Relevance
“…COVID-19 vaccine-associated uveitis has been reported in 27 cases in the peerreviewed literature to date (Table 1), with onset ranging from 1 to 30 days following vaccine administration. [23][24][25][26][27] Twenty-five of the 27 cases received the recombinant mRNA BNT162b2 (Pfizer/ BioNTech) vaccine, while the remaining 2 cases received the adenovirus vector ChAdOx1 nCoV-19 (AstraZeneca) and inactivated virus BBIBP-CorV (Sinopharm) vaccines, respectively. Seventeen cases developed uveitis following the second dose, eight cases following the first dose, while dose administration details were not available for the remaining two cases.…”
Section: Covid-19 Vaccination and Ocular Inflammatory Diseasementioning
confidence: 99%
“…COVID-19 vaccine-associated uveitis has been reported in 27 cases in the peerreviewed literature to date (Table 1), with onset ranging from 1 to 30 days following vaccine administration. [23][24][25][26][27] Twenty-five of the 27 cases received the recombinant mRNA BNT162b2 (Pfizer/ BioNTech) vaccine, while the remaining 2 cases received the adenovirus vector ChAdOx1 nCoV-19 (AstraZeneca) and inactivated virus BBIBP-CorV (Sinopharm) vaccines, respectively. Seventeen cases developed uveitis following the second dose, eight cases following the first dose, while dose administration details were not available for the remaining two cases.…”
Section: Covid-19 Vaccination and Ocular Inflammatory Diseasementioning
confidence: 99%
“… 112–114 In a multi-center study of 23 eyes of 21 patients that developed an acute episode of uveitis after the BNT162b2 vaccine (Pfizer), 8 patients (38%) had a known history of uveitis, the median time to onset was approximately 8 days, and most patients (86%) had mild to moderate anterior uveitis that significantly improved with topical therapy or intravitreal steroids. 115 The authors suggested that the vaccine may have triggered a type I interferon secretion, leading to an autoimmune reaction. 115 There have also been case reports of acute corneal graft rejections occurring after vaccination, which may be due to allorecognition by the direct pathway or incitation of the antibody response; fortunately, most rejection episodes resolved with topical and/or systemic steroids.…”
Section: Vaccine Effectivity and Potential Side Effectsmentioning
confidence: 99%
“… 115 The authors suggested that the vaccine may have triggered a type I interferon secretion, leading to an autoimmune reaction. 115 There have also been case reports of acute corneal graft rejections occurring after vaccination, which may be due to allorecognition by the direct pathway or incitation of the antibody response; fortunately, most rejection episodes resolved with topical and/or systemic steroids. 105 , 112 , 116–120 Physicians may therefore consider reviewing the potential signs of graft rejection with corneal transplant recipients in order to improve earlier detection and treatment.…”
Section: Vaccine Effectivity and Potential Side Effectsmentioning
confidence: 99%
“…Several inflammatory events other than MEWDS have been reported after COVID-19 vaccination. Rabinovitch et al [ 2 ] described 19 patients with anterior uveitis (2 with bilateral inflammation) that developed after vaccination with BNT162b2 mRNA, with 8 cases occurring after the first vaccination and 11 cases after the second vaccination. In our case, bilateral inflammation of the anterior segment was observed, manifested by an increased flare in the anterior chamber.…”
Section: Discussionmentioning
confidence: 99%